Penerapan Metode Praktikum Berbantuan Diagram Vee Untuk Meningkatkan Literasi Sains dan Sikap Sains Siswa Pada Materi Ekosistem Kelas VII SMPIT Bina Ummah - Asih, Senjha Mutiara; Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Edubiologica, 2023)
This study aims to determine the increase in scientific literacy and scientific attitude of students through practicum learning with vee diagrams on ecosystem material. The method used in this research is a quasi-experimental with "static group pretest-posttest design". The research subjects were students of class VII in one of the junior high schools in Cirebon Regency. The sample is 65 students. The results showed that the implementation of practicum learning with the vee diagram was almost entirely carried out in accordance with the practicum stages. Based on the average difference test, the results showed that there was no significant (significant) difference between the average scientific literacy of students in the control class and the experimental class. The data processing techniques used are normality test, homogeneity test, and hypothesis testing (t test). Based on the results of the analysis using Kolmogorov- Smirnova that practical learning with vee diagrams can improve students' scientific literacy on ecosystem materials. The results showed that there was an increase in students' scientific literacy, especially in the aspect of competence in identifying scientific problems by 85%. In the aspect of science attitudes, practicum with vee diagrams is able to improve students' scientific attitudes on indicators of responsibility for resources and the environment. Most students expressed a positive response to the application of practicum learning with the help of vee diagrams on ecosystem material.